Peran Media Sosial Instagram Dalam Kegiatan Penjualan Produk Minuman Di Kafe Kopilikasi Pangeran Jayakarta Bekasi - Rahmi Yuniar; Akhmad Syafrudin Syahri (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Currently, Instagram social media plays an important role as a social media platform and has become a means of marketing communication for companies. Specifically for coffee shop businesses such as Kopilikasi, the research entitled "The Role of Instagram Social Media on the Sales of Beverage Products at Kopilikasi Cafe, Pangeran Jayakarta, Bekasi" has a research objective, namely to find out whether social media plays an important role in marketing activities at Kopilikasi cafes and to find out the content that attracts audiences on Instagram social media. . This research method uses descriptive qualitative methods. The data sources in this research used interviews, observation and documentation. The main theoretical basis in this research is New Media Theory. The results of this research are that Instagram plays an important role in sales at Kopilikasi Cafe. Copying attracts consumers' buying interest by creating content on Instagram. This content is used as a promotional tool containing information about Kopilikasi Cafe. Copylication has a characteristic in its content, namely creating content in a cinematic style. Based on the analysis, researchers draw conclusions, namely content that attracts copycat consumers' buying interest, namely content with copycat consumer objects because it has been proven to be successful in increasing the attention and interest of the audience on Instagram. Currently, Instagram plays an important role in the promotion and sales process of Kopilikasi Cafe and has succeeded in increasing sales and the content created has succeeded in attracting the attention of its audience on Instagram.